ODS – træk af en historisk ordbogs historie - Andersson, Henrik (LexicoNordica, 2006)
The 28-volume historical Ordbog over det danske Sprog (ODS, Dictionary of the Danish Language), by far the most comprehensive dictionary of the Danish language, was initiated c. 1900 by Verner Dahlerup and published 1919–56 by Det Danske Sprog- og Litteraturselskab (DSL, Society for Danish Language and Literature). In 1907, Dahlerup presented his principles for the new dictionary in the periodical Danske Studier (Studies in Danish). From his article it appears that ODS was conceived on a much smaller scale than it proved to be after Dahlerup handed over his project to DSL in 1915. The paper explains to what extent DSL did or did not realize the 1907-principles as to entry structure, definitions, etymology, word usage, foreign words etc.